Negative social tipping dynamics resulting from and reinforcing Earth system destabilization - Spaiser, Viktoria; Juhola, Sirkku; Constantino, Sara M.; Guo, Weisi; Watson, Tabitha; Sillmann, Jana; Craparo, Alessandro; Basel, Ashleigh; Bruun, John T.; Krishnamurthy, Krishna; Scheffran, Jürgen; Pinho, Patricia; et al. (Copernicus Publications, 2024)
In recent years, research on normatively positive social tipping dynamics in response to the climate crisis has produced invaluable insights. In contrast, relatively little attention has been given to the potentially negative social tipping processes that might unfold due to an increasingly destabilized Earth system and to how they might in turn reinforce social and ecological destabilization dynamics and/or impede positive social change. In this paper, we discuss selected potential negative social tipping processes (anomie, radicalization and polarization, displacement, conflict, and financial destabilization) linked to Earth system destabilization. We draw on related research to understand the drivers and likelihood of these negative tipping dynamics, their potential effects on human societies and the Earth system, and the potential for cascading interactions (e.g. food insecurity and displacement) contributing to systemic risks. This first attempt to provide an explorative conceptualization and empirical account of potential negative social tipping dynamics linked to Earth system destabilization is intended to motivate further research into an under-studied area that is nonetheless crucial for our ability to respond to the climate crisis and for ensuring that positive social tipping dynamics are not averted by negative ones.